2022
DOI: 10.2169/internalmedicine.9405-22
|View full text |Cite
|
Sign up to set email alerts
|

Development of Acute Adult T-cell Leukemia Following PD-1 Blockade Therapy for Lung Cancer

Abstract: Immune checkpoint inhibitors (ICIs) are widely used for the treatment of various cancers. However, paradoxical exacerbation of neoplasms, referred to as "hyperprogressive disease," has been reported in a proportion of patients treated with anti-programmed cell death-1 (PD-1)/PD-1 ligand (PD-L1) blockade. We herein report a case of acute adult T-cell leukemia (ATL) that developed shortly after the administration of nivolumab, a PD-1 inhibitor, to treat non-small-cell lung cancer. There were no signs of ATL befo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…Therapeutic approaches using anti–PD-1 antibodies as checkpoint inhibitors have led to rapid hyperprogression in some ATLL cases. 38 , 39 These observations suggested that T-cell receptor signaling might be active but kept in check by the PD-1/PD-L1 axis in such ATLL cases, and anti–PD-1 antibodies would disrupt the equilibrium state. In this context, avelumab may hold an advantage for safety in terms of ATLL treatment due to its dual role of PD-1/PD-L1 blockage and ADCC function.…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutic approaches using anti–PD-1 antibodies as checkpoint inhibitors have led to rapid hyperprogression in some ATLL cases. 38 , 39 These observations suggested that T-cell receptor signaling might be active but kept in check by the PD-1/PD-L1 axis in such ATLL cases, and anti–PD-1 antibodies would disrupt the equilibrium state. In this context, avelumab may hold an advantage for safety in terms of ATLL treatment due to its dual role of PD-1/PD-L1 blockage and ADCC function.…”
Section: Discussionmentioning
confidence: 99%